2013
DOI: 10.1111/bju.12028
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin type A for the treatment of non‐neurogenic overactive bladder: does using onabotulinumtoxinA (Botox®) or abobotulinumtoxinA (Dysport®) make a difference?

Abstract: Objective To compare the clinical effects of two different commercially available botulinum toxin type A products, onabotulinumtoxinA (Botox®; Allergan Inc., Irvine, CA, USA) and abobotulinumtoxinA (Dysport®; Ipsen Ltd, Slough, UK), on non‐neurogenic overactive bladder (OAB). Patients and Methods We included 207 patients, who underwent treatment with botulinum toxin type A for non‐neurogenic OAB from January 2009 to June 2012 at our institution, in a prospective database that recorded details of their prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…Unlike ONA, there is no evidence of the dose ranging trial for ABO in this clinical setting of patients. The doses of these toxins are not equivalent and thus, they can not be considered interchangeable . For this reason, clinical trials are needed to establish the appropriate dose for each formulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike ONA, there is no evidence of the dose ranging trial for ABO in this clinical setting of patients. The doses of these toxins are not equivalent and thus, they can not be considered interchangeable . For this reason, clinical trials are needed to establish the appropriate dose for each formulation.…”
Section: Discussionmentioning
confidence: 99%
“…In urology, onabotulinumtoxinA and abobotulinumtoxinA are the two most commonly used formulations, the first one being the only licensed one in the USA and Europe for NDO and IDO management . However, randomized clinical trials support the use of ABO for NDO, and small uncontrolled studies have reported its use in IDO/OAB …”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge there are no randomized, prospective studies directly comparing different formulations of BTA. Ravindra et al [12] , published a retrospective, non-randomised study comparing BOTOX to DYSPORT for iOAB treatment after their department switched from formulation used. They found similar results, with no difference in the duration of effect, but the DYSPORT cohort had almost twice the rate of symptomatic urinary retention (23 vs. 42%) requiring CIC.…”
Section: Discussionmentioning
confidence: 99%
“…Before injection, the vials of toxin must be reconstituted with preservative-free saline and the mixture can be stored at 2°C–8°C for up to 24 hours. Of note, the product does contain human albumin, which should be disclosed due to the reluctance of some patients to receive this 15. When preparing the mixture, avoid vigorous shaking of the vial to prevent protein denaturation.…”
Section: Injection Techniquementioning
confidence: 99%
“…The two most studied preparations are onabotulinumtoxinA (Botox™, Allergan, Inc., Irvine, CA, USA) and abobotulinumtoxinA (Dysport ® , Ipsen Biopharm Ltd, Slough, UK) 14. There is also no reliable conversion dosing that can be utilized 15. This was shown in a prospective database from Nottingham, UK: the institution switched from Botox to Dysport ® in 2009 and evaluated the comparative efficacy and complications in a group of 207 patients with OAB.…”
Section: Introductionmentioning
confidence: 99%